PENDEKATAN SCIENTIFIC LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Imam Ghozali (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
This paper describes the scientific learning approach in improving student achievement in madrasah. Scientific approach is a strategy used by teachers in learning activities, which is done through a scientific process. Something learned and acquired learners, done with the senses and minds themselves, so that they directly gain knowledge. The scientific approach is one of the characteristics of the application of the 2013 curriculum, in which students are invited to experience firsthand what is being learned from the theory of science through five processes, namely the process of observing, questioning, experimenting, associating, communicating. By inviting students directly, students are expected to easily achieve the purpose of learning, which then has an impact on improving learning achievement.